Improved high-precision mass measurements of mid-shell neon isotopes - Jacobs, Andrew; Andreoiu, C.; Bergmann, J.; Brunner, T.; Dickel, T.; Dillmann, I.; Dunling, E.; Flowerdew, J.; Graham, L.; Gwinner, G.; Hockenbery, Z.; Huang, W. J.; et al. (Nuclear physics. A, Nuclear and hadronic physics, 2023)
New mass values measured with the TITAN MR-TOF-MS are reported for the short-lived isotopes 24−26Ne, produced at TRIUMF's ISAC facility using a uranium carbide target and cold FEBIAD ion source. A least-squares adjustment within the framework of the Atomic Mass Evaluation was performed and the improved precision of the new mass values is highlighted. The improved mass accuracy in this N=14 mid-shell region can also point to the refinement in values of the charge radii. By reducing the mass uncertainty of isotopes, their contribution of the mass shift uncertainty in laser spectroscopy can be negated. The work is part of developments for reaching the N=20 Island of Inversion, where high molecular contamination hinders mass measurements of the neon isotopes.
Gesehen am 13.10.2023